Inherited DNA methylation primes the establishment of accessible chromatin during genome activation - Liu, Guifen; Wang, Wen; Hu, Shengen; Wang, Xiangxiu; Zhang, Yong (Genome Research, 2018)
For animals, epigenetic modifications can be globally or partially inherited from gametes after fertilization, and such information is required for proper transcriptional regulation, especially during the process of zygotic genome activation (ZGA). However, the mechanism underlying how the inherited epigenetic signatures affect transcriptional regulation during ZGA remains poorly understood. Here, we performed genome-wide profiling of chromatin accessibility during zebrafish ZGA, which is closely related to zygotic transcriptional regulation. We observed a clear trend toward a gradual increase in accessible chromatin during ZGA. Furthermore, accessible chromatin at the promoters displayed a sequential priority of emergence, and the locations of the accessible chromatin were precisely primed by the enrichment of unmethylated CpGs that were fully inherited from gametes. On the other hand, distal regions with high methylation levels that were inherited from the sperm facilitated the binding of DNA methylation-preferred transcription factors, such as Pou5f3 and Nanog, which contributed to the establishment of accessible chromatin at these loci. Our results demonstrate a model whereby inherited DNA methylation signatures from gametes prime the establishment of accessible chromatin during zebrafish ZGA through two distinct mechanisms.